PATTERNS OF CACTACEAE SPECIES DISTRIBUTION IN A PROTECTED AREA IN THE SEMIARID CAATINGA BIOME OF NORTH-EASTERN BRAZIL. (22nd June 2016) - Ribeiro-Silva, S.; Medeiros, M. B.; Lima, V. V. F.; Peixoto, M. R.; Aona, L. Y. S.
Abstract : Although Brazil is the centre with the third highest diversity of Cactaceae, the distribution of species at the local scale in Brazil remains largely unknown. This article describes the distribution patterns of the Cactaceae communities in the protected area of the Contendas do Sincorá National Forest (CSNF) in a semiarid region in the north-east of Brazil. Trails were distributed between the altitudes of 290 and 596 m, along which 91 plots (1.8 ha) were established for quantitative surveys. The floristic data were also recorded separately on these trails. With the floristic survey, 18 taxa were recorded, and the quantitative surveys within the plots identified 10 species, represented by 1135 individuals. The distribution patterns of the species of Cactaceae were intermittent, which provided a likely explanation for the differences between the floristic survey and the species composition of the plots. The largest fraction of the floristic variation was not explained by environment or space, and this may be related to climatic alterations in the past, evolutionary processes, natural and anthropic disturbances and other unmeasured environmental variables. The recorded endemic, vulnerable and endangered species of the caatingas of Bahia indicate that broader protection areas for the Cactaceae species in the region of the CSNF are necessary.